The effect of company-specific factors on financial leverage: Evidence from industrial sector Malaysia - Nurul Najwa, Roslee (2016)
The main objective of this thesis is to examine the influence of company-specific on financial leverage of 88 industrial product companies listed in Bursa Malaysia. This study covers an observation period of 10 years (2005-2015) on panel data basis. Dynamic panel regression is applied as System General Method of Moment (S-GMM) suggesting that the research model is genuinely dynamic. The results of the study indicates that all variables Age (SUSAgei,t), EPS Growth (SUSEPSgi,t), Total Asset (SIZETAi,t), Net Profit Margin (PRONPMi,t,), ROE (PROROEi,t), Quick Ratio (LIQRi,t,), Cash ratio (LICashRi,t) and Prior Leverage (LagLEVi,t-1) are significantly affecting the financial leverage (LEVi,t ). However, variables Age (SUSAgei,t), Total Asset (SIZETAi,t), Net Profit Margin (PRONPMi,t,), and Quick Ratio (LIQRi,t,) have a negative association with the leverage. Results of SUSEPSg, SIZETA, PRONPM, PROROE and LIQR support the pecking order theory while variables SUSAge, LICashR and LagLEVi,t-1 support the trade-off theory. General outcome of this study reveals that company specific factors are affecting leverage.